Acetaminophen synthesis and encapsulation using safe mixed-solvents and solution enhanced dispersion by supercritical CO2 - Islam, Tariqul; Sarker, Md. Zaidul Islam Sarker; Helal Uddin, A.B.M.; Lee, Richard Smith Jr (Elsevier B.V., 2022)
Acetaminophen (ACMP) was synthesized in mixed-solvents (H2O-acetone, H2O-dimethyl sulfoxide, H2O-isopropyl alcohol) for purposes of eliminating hazardous dipolar aprotic solvents. The H2O-acetone solvent-pair gave synthesized ACMP yields of 79.2%. Synthesized ACMP samples were encapsulated using solution enhanced dispersion by supercritical CO2 (SEDS) at 150 bar, 45 ◦C, 1.5 mL/min feed flow rate (30 mg ACMP/mL in mixed-solvent), CO2 flow rate of 15 L/min (1 bar, 25 ◦C) in which suitable products could not be formed with PEG-4000 excipient at ACMP:PEG ratios of 1:1 with mixed-solvents, however, with ethyl cellulose (EC) excipient at ACMP:EC ratios of 1:1 and ethanol-acetone mixed-solvent (x:y, v/v, x = 1–9, y = 9–1), encapsulated products could be formed over the full range of mixed-solvent compositions. ACMP encapsulated fine particles had purities as high as 99.9% demonstrating that SEDS with safe mixed-solvents can broaden methods available for encapsulating pharmaceuticals.